ROS 2017
DOI: 10.20455/ros.2017.805
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intermittent Hypoxia, Reactive Oxygen Species, and Oxygen-Induced Retinopathy

Abstract: Most of the major morbidities in the preterm newborn are caused by or are associated with oxygen–induced injuries and are aptly called “oxygen radical diseases in neonatology or ORDIN”. These include bronchopulmonary dysplasia, retinopathy of prematurity, periventricular leukomalacia, intraventricular hemorrhage, necrotizing enterocolitis and others. Relative hyperoxia immediately after birth, immature antioxidant systems, biomolecular events favoring oxidative stress such as iron availability and the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 141 publications
0
18
0
Order By: Relevance
“…On the other hand, in the early stages of life after birth, there is an exponential increase in reactive oxygen species (ROS) [ 35 ], which may be responsible for serious alterations that are very well described in the human neonate [ 36 , 37 ], calves [ 38 ] and canine newborns [ 35 ]. Among the components of colostrum, there are different essential antioxidants against oxidative damage [ 38 , 39 ]; however, the antioxidant potential of CCM exosomes has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the early stages of life after birth, there is an exponential increase in reactive oxygen species (ROS) [ 35 ], which may be responsible for serious alterations that are very well described in the human neonate [ 36 , 37 ], calves [ 38 ] and canine newborns [ 35 ]. Among the components of colostrum, there are different essential antioxidants against oxidative damage [ 38 , 39 ]; however, the antioxidant potential of CCM exosomes has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nitric oxide (NO) may combine with oxygen free radicals, especially the superoxide anion, to form peroxynitrite (ONOO − ), a reactive nitrogen species (RNS). ROS and RNS rapidly oxidize nucleic acids, lipids, and proteins, thereby altering their structure and function and modifying the normal cellular redox status, leading to increased OS [7] (Figure 1).…”
Section: Aerobic Metabolism Reactive Oxygen Species and Oxidativmentioning
confidence: 99%
“…The steroid hormone estrogen regulates many functionally unrelated processes in numerous tissues, and exogenous estrogen and some estrogen receptor agonists have been reported to be effective in promoting retinal vascular growth and treating ROP by our and other studies. [ 5–8 ] Our previous study indicated that treatment with 17β‐E2 (an estrogen receptor agonist) could reduce oxidative stress, an important regulator in the pathogenesis of ROP, [ 9 ] in the hyperoxic phase of oxygen‐induced retinopathy (OIR). [ 6 ] G‐protein‐coupled estrogen receptor (GPER/GPR30) is uniquely localized to the endoplasmic reticulum (ER), where it specifically binds estrogen to regulate the function of ER, contributing to normal estrogen physiology as well as pathophysiology.…”
Section: Introductionmentioning
confidence: 99%